REGULASI EMOSI DALAM STRATEGI COPING STRESS BAGI NARAPIDANA DALAM PEMBINAAN KEPRIBADIAN - Seno, Ario Bimo; Rahayu, Mulyani (Journal of Management Small and Medium Enterprises (SMEs), 2024)
Emotional regulation is the ability to control and adjust emotions that arise and adjust them to an appropriate level of intensity to achieve a goal. Prisoners will live a life that is different from their previous life, including loss of relationships with opponents, loss of the right to own goods, and loss of a sense of security. Qualitative research is a research process that produces descriptive data about people through written or oral speech and observable behavior. Prisoners can recognize, feel and know the emotions they experience when emotions arise such as sadness, anger, joy, etc. Prisoners can know how to tolerate feelings of frustration when they arise. Prisoners can have a responsible nature for whatever they do and also always be optimistic in everything. The results of emotional regulation in religious coping in prisoners have been implemented well, prisoners have made changes in their responses by implementing praying, dhikr, and reading the Koran and taking part in physical training as a way to reduce the negative emotions he experiences. Personality development through physical development is also going well, where physical development is carried out routinely and in a structured manner. Keywords: Coping Stress; Emotion Regulation; Personality Development